Kartini in the Pandemic: Women's Economic Empowerment Through Synergy of Digital Banking, Fintech, and E-Commerce - Alex Fahrur Riza; Dwi Marlina Wijayanti (Journal of Islamic Economy and Community Engagement, 2022)
The role of the Financial Services Authority (OJK) is getting bigger in Indonesia. Various strategies are implemented to increase financial inclusion and literacy in Indonesia. However, the mindset that is built that women are identical to housewives who do not have financial independence creates a gap in inclusion and financial literacy between men and women. As a result, women cannot contribute to managing finances well and cannot help build a strong family economy because they do not have the knowledge and financial skills as well as men. The KARTINI program is a program that provides facilities for the women's community to have financial independence. The integration between digital banking (smart behavior), financial technology (affiliate marketing), and e-commerce (dropship) can be the right program in optimizing financial inclusion and literacy for women. The implementation of the KARTINI program has a positive impact on the women's community such as women's cooperatives, PKK women, Aisyiyah women, recitation groups, dharma Wanita and other women's groups. In addition, this program can be applied by OJK to all regions in Indonesia to increase financial literacy and inclusion. Through the integration of smart behavior, affiliate marketing, and dropship, the goals of OJK will be achieved more quickly.